AN ECONOMIC STUDY OF THE RELATIONSHIP BETWEEN AGRICULTURAL IMPORTS AND AGRICULTURAL PRODUCT IN IRAQ FOR THE PERIOD 1991-2018 USING TODA-YAMAMOTO CAUSALITY TEST - & et al., Alattabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aims to analyze empirically the causality relationship between agricultural imports and agricultural product in Iraq for the period 1991-2018 basing on the causality developed by Toda – Yamamoto. Results indicated that there is a bidirectional causality relationship between agricultural imports and agricultural product, throw the value of chi-square which was 5.6 in case of the dependent variable is agricultural product, and this value was significant at 5% level. While the value of chi-square was 6.2 in case of the dependent variable is agricultural imports, and it is significant also at 5% level. That means there is a bidirectional causality relationship between the two variables in Iraq. The study recommended that it is necessary int to interest to import the investment agricultural goods in order to support agricultural production, and to increase the level of self-sufficiency in Iraq.